1970
DOI: 10.1002/jhet.5570070346
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constitution and activity of bipyridylium herbicides. Part VI. Diquaternary salts of 4,4′‐iminodipyridine and 4,4′‐thiodipyridine

Abstract: 19In work reported in earlier papers of this series (1-5) much evidence has bc:r:n obtained to support the view that thc mode of action of the bipyridylium herbicides, paraquat (I) and diquat ([I), is connected with their ability to be reduced in aqueous solution to stable radical cations by a onr: electron transfer which is reversed by air. The effect on herbicidal activity of the introduction between the pyridine rings of paraquat of a group which is capable of acting as an electron transfer bridge has so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The stability of the radical cations is due to the delocalization of the odd electron over both pyridine rings which are essentially coplanar. The introduction between the pyridine rings of diquat or paraquat of an atom or group which is capable of acting as an electron transfer bridge usually results in loss of herbicidal activity since diquaternary salts of this type give, inter alia, unstable radical cations on reduction (3)(4)(5)(6)(7)(8)(9). Recently, however, it was found that the introduction of the planar 1,3,5-triazine ring system between the pyridine rings of paraquat gave the salt (IV) which showed very good herbicidal activity (10).…”
mentioning
confidence: 99%
“…The stability of the radical cations is due to the delocalization of the odd electron over both pyridine rings which are essentially coplanar. The introduction between the pyridine rings of diquat or paraquat of an atom or group which is capable of acting as an electron transfer bridge usually results in loss of herbicidal activity since diquaternary salts of this type give, inter alia, unstable radical cations on reduction (3)(4)(5)(6)(7)(8)(9). Recently, however, it was found that the introduction of the planar 1,3,5-triazine ring system between the pyridine rings of paraquat gave the salt (IV) which showed very good herbicidal activity (10).…”
mentioning
confidence: 99%